Quality of Immediate Postoperative Nursing Care for Patients in Public and Private Hospitals in Erbil City, Iraq- Comparative Study - Sideeq Sadir Ali (Hawler Medical University, 2020)
Background and objective: The 1 to 2 hours for the first 24 hours after surgical operation is a crucial time to perform patient care. The study aimed to assess and compare quality of immediate post-operation nursing care for patients undergoing surgeries in the public and private hospitals in Erbil City. Methods: A comparative study design was conducted on non-probability and purposive sample of 106 nurses (53 nurses of public hospitals and 53 nurses from private hospitals) in the surgical unit in all public and some private hospitals in Erbil city. The data was collected between February and July, 2019 by direct observation and using an observational questionnaire. Results: The majority of the nurses were young adults who had graduated from a nursing institute who were of middle income and lived in an urban area. The duration of experience as a nurse was between 1 to 10 years. The majority of the nurses (98.1%) in the pub-lic hospitals they practiced poor nursing care practice, while most of the nurses (69.8) in the private hospitals practiced good nursing care practices. Very high significant difference found between immediate post-operation nursing care in public and private hospitals (P <0.000). Conclusion: The study concluded that; postoperative nursing care is very important to improve health services, but the quality of the nursing care in the public hospitals as a generally was very poor when compared with the private hospitals. We recommended improving their skills by implementation job description, opening training course and monitoring of the nurses as well as awareness and follow-up.